Extracurricular Management as an Internal Strategy for Strengthening Madrasah Image: A Case Study at MAN 2 Probolinggo - Nasihin Robiati, Siti Sururin; Sutiah, Sutiah; Hady, M. Samsul (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study analyzes extracurricular management practices, integrative management strategies, and the internal mechanisms perceived to support institutional branding at MAN 2 Probolinggo. Design/methods/approach – This study employed a qualitative approach with a single-case study design. Data were obtained from 11 purposively selected informants through semi-structured interviews, observations, and documentation. The data were analyzed through inductive and deductive coding using the planning, organizing, actuating, and controlling functions and the Positive Youth Development perspective. Data trustworthiness was strengthened through triangulation, informant confirmation, peer review, and expert examination. Findings – Extracurricular activities were managed through student potential mapping, competency-based role allocation, flexible coaching, and continuous monitoring and evaluation. The integrative strategy linked achievement and character development, academic coordination, stakeholder support, and digital publication. The synthesis of the findings produced the Achievement- and Publication-Based Management Model (MMBPP) as an analytical framework. These findings explain the internal mechanisms perceived to support visibility, reputation, and institutional branding, but do not directly demonstrate changes in public image. Research implication – This study integrates extracurricular management, student development, and institutional communication within a single contextual conceptual framework. Madrasahs with comparable characteristics may consider documented potential mapping, clear role allocation, evaluation of achievement and character, academic coordination, and credible publication of accomplishments.